Single pulse heating of a nanoparticle array for biological applications. Issue 9 (22nd February 2022) - Xie, Chen; Kang, Peiyuan; Cazals, Johan; Castelán, Omar Morales; Randrianalisoa, Jaona; Qin, Zhenpeng
Abstract : This study focuses on the effect of single pulse heating of nanoparticle array on biological activity. The analysis demonstrates that nanoscale-confined heating may lead to targeted protein denaturation, whereas it does not give targeted activation of the thermally-sensitive TRPV1 channel. Abstract : With the ability to convert external excitation into heat, nanomaterials play an essential role in many biomedical applications. Two modes of nanoparticle (NP) array heating, nanoscale-confined heating (NCH) and macroscale-collective heating (MCH), have been found and extensively studied. Despite this, the resulting biological response at the protein level remains elusive. In this study, we developed a computational model to systematically investigate the single-pulsed heating of the NP array and corresponding protein denaturation/activation. We found that NCH may lead to targeted protein denaturation, however, nanoparticle heating does not lead to nanoscale selective TRPV1 channel activation. The excitation duration and NP concentration are primary factors that determine a window for targeted protein denaturation, and together with heating power, we defined quantified boundaries for targeted protein denaturation. Our results boost our understandings of the NCH and MCH under realistic physical constraints and provide robust guidance to customize biomedical platforms with desired NP heating.